SOME FACTORS AFFECTING INTENSIVE REARING ADOPTION ON BEEF CATTLE FARMERS IN WAJO REGENCY, SOUTH SULAWESI PROVINCE - Baba, S.; Dagong, M.I.A.; Risal, M. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
Land use conflict among agriculture and animal husbandry caused beef cattle must be keptintensively. The objective of this research was to identify adoption level of beef cattle intensive rearingand some factors that affecting farmers adoption. Research design was survey with 90 respondents froma total of 578 farmers. Data were obtained through interview and observations using questionnare withclose question. The data were analyzed with multiple regression models. The level of intensive rearingadoption (dependent variable) was measured based on housing system, feeding, reproduction, healthmanagement and feces utilization. While, independent variables were based on the intensity ofextension, relative adventage, subjective norm, control of behavior, attitude, age, land area and scale ofbusiness. Level of housing system, feeding, reproduction and health management were in the medium level (average >50% of farmers), while feces utilization was in the lowest level. Factors that positivelyaffected farmer adoption in Wajo regency were the ability of the farmers to control their behavior(p<0.01), farmer position in social community or subjective norm and relative adventage weresignificant with p<0.05. Another case with contact to the extension, age, attitude, land area and scale ofbusiness were no significant affected farmers adoption. To enforce adoption of intensive rearingtechnology, extension program should be developed to influence farmers psychology such profit level ofintensive rearing and convenience on cattle handling.